Magnesium intake decreases Type 2 diabetes risk through the improvement of insulin resistance and inflammation: the Hisayama Study. Issue 12 (29th June 2013) - Hata, A.; Doi, Y.; Ninomiya, T.; Mukai, N.; Hirakawa, Y.; Hata, J.; Ozawa, M.; Uchida, K.; Shirota, T.; Kitazono, T.; Kiyohara, Y.
Abstract Aims Early studies have shown that magnesium intake decreases the risk of Type 2 diabetes, but the results are still inconsistent. We prospectively examined the association between magnesium intake and incidence of Type 2 diabetes in a general Japanese population. Methods A total of 1999 subjects without diabetes aged 40–79 years who underwent a 75‐g oral glucose tolerance test were followed up prospectively for a mean of 15.6 years. Results During the follow‐up, 417 subjects developed Type 2 diabetes. The age‐ and sex‐adjusted incidence of Type 2 diabetes significantly decreased with increasing magnesium intake quartile levels (≤ 148.5, 148.6–171.5, 171.6–195.5 and ≥ 195.6 mg/day, P for trend = 0.01). In multivariate analyses, after adjusting for comprehensive risk factors and other dietary factors, the hazard ratio of Type 2 diabetes was 0.67 (95% CI 0.49–0.92; P = 0.01) in the third quartile and 0.63 (95% CI 0.44–0.90; P = 0.01) in the highest quartile compared with the first quartile. In addition, the risk of Type 2 diabetes was 14% lower (P = 0.04) for a 1‐sd increment of log‐transformed magnesium intake in the multivariate‐adjusted model. In stratified analysis, there were statistically significant interactions between magnesium intake and levels of homeostasis model assessment of insulin resistance, high‐sensitivity C‐reactive protein or alcohol intake on the risk of Type 2 diabetes (all P < 0.05). Conclusions Our findings suggest that increased magnesium intake was a significant protective factor for the incidence of Type 2 diabetes in the general Japanese population, especially among subjects with insulin resistance, low‐grade inflammation and a drinking habit.